2003
DOI: 10.1021/bi035790e
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, pH-Dependent RNA Ligation by the VS Ribozyme in Trans

Abstract: The VS ribozyme acts as a very efficient ligase in trans when the 5' cleavage product is prevented from dissociation by an extended helix Ia in the substrate. Provided that the length of this helix is >or=10 bp, the substrate becomes approximately 80% ligated by the ribozyme acting in trans. Most of the nucleotides that have been shown to be important for cleavage are similarly important for ligation, including the critical A756 of the active site. The exception to this is C755. The variant ribozyme C755A has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 27 publications
6
30
0
Order By: Relevance
“…There could be an element of induced fit on binding that would improve the ribozyme-substrate interaction further. Helix Ia of the substrate essentially protrudes unhindered from the lower end of the complex; we have found that this helix can be extended considerably without loss of catalytic activity, consistent with this prediction (McLeod and Lilley 2004). Helix I can be attached to the ribozyme in a number of different ways with preservation of activity.…”
Section: The Interaction Between Ribozyme and Substratesupporting
confidence: 83%
See 2 more Smart Citations
“…There could be an element of induced fit on binding that would improve the ribozyme-substrate interaction further. Helix Ia of the substrate essentially protrudes unhindered from the lower end of the complex; we have found that this helix can be extended considerably without loss of catalytic activity, consistent with this prediction (McLeod and Lilley 2004). Helix I can be attached to the ribozyme in a number of different ways with preservation of activity.…”
Section: The Interaction Between Ribozyme and Substratesupporting
confidence: 83%
“…Clearly, A756 must be a candidate for this role in the VS ribozyme. The rate of the cleavage reaction is not significantly dependent on pH (Rastogi and Collins 1998), unlike that for the hammerhead reaction (Dahm et al 1993), but pH dependence corresponding to a pK a of 5.6 has been observed for the ligation reaction (McLeod and Lilley 2004). The restoration of good ligation activity in VS ribozyme variants with nucleotide bases of reduced pK a at lowered pH and stimulation of activity in variants with nucleotide bases of increased pK a point to a requirement for a protonated base at position 756 (Jones and Strobel 2003).…”
Section: Possible Catalytic Mechanismsmentioning
confidence: 91%
See 1 more Smart Citation
“…The reaction is initiated when an O2' atom attacks the adjacent phosphorus in an SN2 transesterification reaction leading to the formation of a 2'3'-cyclic phosphate and a 5' hydroxyl group (Figure 1). Ligation is the reverse of this reaction (26)(27)(28)(29)(30), and occurs if the cleavage product RNA is held in place by the structure of the ribozyme. The hammerhead (31,32), hepatitis delta virus (HDV) (33,34) and twister (12) …”
Section: The Nucleolytic Ribozymesmentioning
confidence: 99%
“…Most previously characterized versions of the Neurospora VS ribozyme showed rather slow cis-or trans-cleavage apparent rate constants (k obs ) in the range of 1 min Ϫ1 or less and were only slightly affected by pH between pH 5.5 and 9.0 (7); however, a trans-ligating construct did exhibit pH dependence below pH 7.0 (8). Other observations have also raised the possibility that a protonated group could be involved in the rate-limiting step of a VS ribozyme reaction pathway.…”
mentioning
confidence: 99%